The impact of economic crisis on momentum strategy and profitability in global stock market : Differences in momentum strategy profitability in developed and emerging markets - Anttila, Nuutti (My University, 2025)
The thesis examines how market crises affect the profitability of the momentum strategy in different markets. It also considers the impact of the COVID-19 pandemic and compares it to previous market crises. The momentum strategy assumes that high-performing stocks will continue to rise, and low-performing stocks will continue to fall in the short term. The strategy has been shown to be effective in normal market conditions, but its performance deteriorates in uncertain times. The paper analyses previous research on investor and market behavior in developed and emerging markets. The aim is to observe how market changes affect the profitability of the momentum strategy and to compare differences across markets. Previous studies have found a decline in the profitability of momentum strategies during market crises and identified significant regional differences in their performance. A significant reason for the collapse of the momentum strategy is the irrational behavior of investors and increasing market volatility. These challenge the continuation of a predictable trend and can lead to losses for the strategy. Despite these challenges, the strategy has historically been profitable in stable market conditions.
Keywords: strategies; COVID-19; pandemics; profitability; economic crises; financial markets; investors; emerging markets; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Kauppatieteiden kandidaattiohjelma|en=Bachelor Programme in Business Studies|